The gut-kidney axis in urolithiasis: roles of gut microbiota, metabolites, and therapeutic implications - Li, Dong; Li, Zehong; Liu, Wei (Frontiers in Microbiology, 2025)
Urolithiasis affects 2–20% of the global population and recurs frequently. Emerging evidence positions the gut–kidney axis as a central driver of stone formation. This review synthesizes epidemiological data, comparative metagenomic analyzes, and mechanistic studies to demonstrate that stone formers exhibit reduced α-diversity, depletion of oxalate-degrading taxa (e.g., Oxalobacter, Lactobacillus, Bifidobacterium), and enrichment of pro-inflammatory genera (Escherichia, Bacteroides). Microbial metabolites—oxalate, short-chain fatty acids, p-cresol, and secondary bile acids—modulate intestinal oxalate transport, systemic inflammation, and renal crystal nucleation. Therapeutic modulation via targeted probiotics, prebiotics, engineered Lactobacillus, or fecal microbiota transplantation restores oxalate homeostasis and attenuates nephrolithiasis in rodent models; however, human efficacy remains preliminary. Large-scale multi-omics cohorts and randomized controlled intervention trials are imperative to translate gut-centric strategies into precision urology.